The peroxisome: an update on mysteries 2.0 - Islinger, Markus; Völkl, Alfred; Fahimi, H. Dariush; Schrader, Michael (Histochemistry and cell biology, 2018)
Peroxisomes are key metabolic organelles, which contribute to cellular lipid metabolism, e.g. the β-oxidation of fatty acids and the synthesis of myelin sheath lipids, as well as cellular redox balance. Peroxisomal dysfunction has been linked to severe metabolic disorders in man, but peroxisomes are now also recognized as protective organelles with a wider significance in human health and potential impact on a large number of globally important human diseases such as neurodegeneration, obesity, cancer, and age-related disorders. Therefore, the interest in peroxisomes and their physiological functions has significantly increased in recent years. In this review, we intend to highlight recent discoveries, advancements and trends in peroxisome research, and present an update as well as a continuation of two former review articles addressing the unsolved mysteries of this astonishing organelle. We summarize novel findings on the biological functions of peroxisomes, their biogenesis, formation, membrane dynamics and division, as well as on peroxisome-organelle contacts and cooperation. Furthermore, novel peroxisomal proteins and machineries at the peroxisomal membrane are discussed. Finally, we address recent findings on the role of peroxisomes in the brain, in neurological disorders, and in the development of cancer.